Kajian Etnobotani pada Masyarakat Lokal Dusun Segenter, Desa Sukadana, Kabupaten Lombok Utara - Deyalis Almahira; Sukiman; Kurniasih Sukenti (Program Magister Ilmu Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2024)
Traditional use of plants by people in Indonesia has been carried out for centuries. There are several areas on Lombok Island with local knowledge regarding the use of plants that has not been revealed, one of which is Dusun Segenter, Sukadana Village, North Lombok Regency. This research aims to reveal aspects of utilization, examine socio-cultural aspects, as well as local wisdom in plant management by the people of Dusun Segenter. This research was carried out by collecting data through observation, structured interviews, open ended, and documentation. Determining informants used purposive sampling and snowball sampling techniques. Data analysis was carried out descriptively based on observations and interviews, while quantitative data analysis was carried out by calculating the Index of Cultural Significance (ICS), Fidelity level (FL), and calculating percentages for plant parts, habitat and cultivation status. The results of the research showed that there were 10 categories of plant utilization involving 76 species from 36 families. These plants are used as food, medicine, tradition, firewood, animal feed, handicrafts, natural dyes, natural pesticides, construction materials for traditional houses in Segenter, and fences. The highest ICS score belongs to Gigantochloa atter (Hassk) Kuzr ex Munro, at 76. Meanwhile, some utilization category have more than one species with maximum value of 100%. Socio-cultural values and local wisdom are reflected in terms of mutual cooperation, sharing, and prayer before carrying out traditional ritual activities, the use of plants as medicine, construction construction, and the erection of fences. This research is expected to support the preservation of biological and cultural resources. Keyword: ethnobotany, local wisdom, Index of Cultural Significance, Fidelity Level